2003
DOI: 10.1177/000348940311200304
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Ranula with Intracystic Injection of the Streptococcal Preparation Ok-432

Abstract: Intracystic injection of OK-432 was developed as a therapy for operatively difficult lymphangioma (cystic hygroma) and is currently becoming a treatment of first choice for this disease. We tried this therapy in 32 patients with ranula (oral floor type in 21 cases and plunging type in 11 cases). Disappearance or marked reduction of the lesion was observed in 31 patients (97%) who had this therapy, and local scarring did not occur in any patient. As side effects, local pain at the injection site and fever (37 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
76
3
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 10 publications
1
76
3
4
Order By: Relevance
“…OK-432 produces inflammation and fibrosis, and injection into the lumen of ranula was successful in 73% of oral ranulas [36][37][38] and 59% of plunging ranulas. [36][37][38]55,57,[81][82][83] Fukase et al 36 observed that patients who had clinical evidence of a strong local inflammatory reaction showed an obvious curative effect, which indicates that there is an increase of the chronic inflammatory reaction present in the ranula in which macrophages break down extravasated mucus, which would increase the removal of extravasated mucus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OK-432 produces inflammation and fibrosis, and injection into the lumen of ranula was successful in 73% of oral ranulas [36][37][38] and 59% of plunging ranulas. [36][37][38]55,57,[81][82][83] Fukase et al 36 observed that patients who had clinical evidence of a strong local inflammatory reaction showed an obvious curative effect, which indicates that there is an increase of the chronic inflammatory reaction present in the ranula in which macrophages break down extravasated mucus, which would increase the removal of extravasated mucus.…”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38]55,57,[81][82][83] Fukase et al 36 observed that patients who had clinical evidence of a strong local inflammatory reaction showed an obvious curative effect, which indicates that there is an increase of the chronic inflammatory reaction present in the ranula in which macrophages break down extravasated mucus, which would increase the removal of extravasated mucus. Fukase et al 36 also observed that the viscosity of the fluid in the ranula increased, and they suggested that fibrinous exudate produced by the inflammation sealed the leak. The cytokines produced by the inflammation would also stimulate the granulation tissue in the wall of the ranula, and the resultant fibrosis could permanently seal the leak.…”
Section: Discussionmentioning
confidence: 99%
“…Removing of a ranula without causing rupture can be a tedious and time-consuming process (Choi and Oh 2003). Watanabe et al (2002) and Fukase et al (2003) reported that intracystic injection therapy with OK-432 is relatively safe and can be used as a substitute for surgery in the treatment of ranulas. Alternatively, the ranula can be treated with the placement of a silk suture or seton into the dome of the cyst (Morton and Bartley 1995;Haberal et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Intracystic injection therapy with OK-432 is relatively safe and can be used as a substitute for surgery in the treatment of ranula. [5] The most common complications is the recurrence of the lesion (5.78%) and sensory deficit of the tongue (4.89%), followed by damage of Wharton's duct (1.82%). Postoperative haematoma, infection, or dehiscence of the wound were seldom seen.…”
Section: Discussion Of Managementmentioning
confidence: 99%